The preservative effects of chitosan film incorporated with thinned young apple polyphenols on the quality of grass carp (Ctenopharyngodon idellus) fillets during cold storage: Correlation between the preservative effects and the active properties of the film. (September 2018) - Sun, Lijun; Sun, Jiaojiao; Liu, Dongjie; Fu, Minghai; Yang, Xi; Guo, Yurong
Graphical abstract: Highlights: Chitosan-polyphenol film showed preservative effects on grass carp fillets. The film delayed degradation of myofibrillar protein and its functional properties. The film delayed loss of textural properties and amino acids of grass carp fillets. The film preservative effects are correlated to its physicochemical properties. Abstract: This study aims to investigate the preservative effects of chitosan film incorporated with thinned young apple polyphenols (YAP) on grass carp fillets (GCF) quality during cold storage. The results showed that the chitosan-YAP film wrapping effectively retarded the microbial proliferation, lipid and protein oxidation, changes in pH and color values and decrease in water holding capacity of GCF during cold storage. Besides, the wrapping with chitosan-YAP film could significantly delay the decrease in the content and functional properties of soluble myofibrillar protein, the loss of the texture and amino acids, and the adverse changes in the surface morphology and sensory values of GCF. Through correlation analyses, the preservative effects of the film may be attributed to its water retention capacity, antioxidant and antibacterial activities. Therefore, the chitosan-YAP film has a potential as a packaging material to extend shelf life of freshwater fish fillets during cold storage.